Percutaneous CT-guided or endoscopic spinal biopsy with accurate pathogen detection for spinal infection - Chen, Jinmei; Guo, Qingxin; Tian, Luying; Shen, Leer; Zhang, Yi; Jiao, Qiong; Lian, Xiaofeng; Chen, Xiaohua (Frontiers in Neurology, 2025)
AimsIn this study, we aimed to analyze the pathogen detection results in spinal infections using percutaneous CT-guided biopsy or transforaminal endoscopic spinal biopsy.MethodsThis is a retrospective observational study of patients who underwent biopsy for spinal infection at Shanghai Sixth People’s Hospital between December 2020 and June 2024. Data on demographics, clinical presentations, radiological findings, and histopathology were collected from medical records. Pathogen detection results from different sampling methods were evaluated.ResultsA total of 131 cases of spinal infection were included in the study. The average age of the patients was 59.1 ± 13.8 years. The median time from symptom onset to diagnosis was 2 months [inter-quartile range (IQR): 1 to 4.5 months]. Clinical manifestations included pain (100%) and fever (15.27%), with the lumbar vertebra being the most commonly affected site (110/168, 65.48%). Elevated ESR, CRP, and IL-6 levels were observed in most cases. MR showed high sensitivity (90.90%) but low specificity (2.04%). Pathogen detection was performed using next-generation sequencing (mNGS) and/or microbial culture. Of the 131 patients, 66 underwent percutaneous CT-guided biopsy, and 65 underwent transforaminal endoscopic spinal biopsy. All samples were tested using mNGS, while microbial culture was performed only on abscess samples from CT-guided biopsy cases. The most commonly identified pathogens were Mycobacterium tuberculosis (18.9), Staphylococcus (17.9), and Streptococcus (10.5). The positive detection rates using mNGS were 51.52% for percutaneous CT-guided biopsy and 50.77% for transforaminal endoscopic biopsy, whereas the culture-positive rates were 41.67 and 42.86% on abscess samples, respectively. There is no significant difference in the positive rates between the two biopsy techniques (χ2 = 0.007292, p = 0.9319). But the detection rate of Mycobacterium under CT-guided biopsy is higher (18.18% vs. 9.23%).ConclusionAccurate pathogen diagnosis is crucial for the diagnosis and treatment of spinal infections. The microbiological detection rates of samples obtained via percutaneous CT-guided are similar to those obtained through transforaminal endoscopic spinal biopsy.